Curriculum Change in Indonesia: Study on Competence-Based Curriculum in Islamic Education (An Overview from Theoretical and Practical Points) - Dahlena Sari Marbun; Kholis Tohir (Budapest International Research and Critics University, 2022)
With regard to the quality of students and graduation, T. Raka Joni (1992) states that the educational process is an effort to produce Indonesian people who have self-confidence and have a learning culture in society so that they can kill creative, innovative behavior, and the desire to progress in accordance with which is listed in the 1993-1998 GBHN. There are 4 (four) learning models, each of which is very creatively used according to the type of material being taught, as well as the extent to which the material is sufficient. The four models are as follows: procedural, hierarchical, horizontal, and combination. By presenting this simple article, it is hoped that teachers can carry out learning activities effectively and efficiently by combining (an effort to combine several strategies in one learning time). So that the use of varied learning strategies will be able to create pleasant learning conditions